Teamwork of General and Special Education Teachers in Managing the Education of Learners with Autism - John Lester Gaviola; Genelyn Lacuña; Sharmaine Manigos (RSF Press, 2024)
Understanding the dynamics of collaboration helps identify best practices, resolve issues, and foster smooth working relationships among general and special education teachers for students with ASD achievement. This study explored the collaboration of general and special education teachers in educating learners with autism spectrum disorder (ASD) at three (3) selected elementary schools in Chicago, Illinois, USA, during the school year 2023-2024. This is a phenomenological inquiry of the ten purposively selected participants who answered the researcher-made semi-structured questionnaire that contained four (4) open-ended questions. Findings showed that in terms of the participants' views about the various collaboration models Implemented in educating learners with autism, the following were the emerging themes: 1) Team Teaching Collaboration, 2) Support Mechanisms on Demand, and 3) Structured Consultation Session. The impact of teacher collaboration on learners with autism academic outcomes were: 1) Enhanced Communication Abilities; 2) Active School Involvement; and 3) Self-sufficiency Development. The barriers encountered to effective collaboration were 1) Challenges in Communication, 2) Support and Policy from the Administration, and 3) Scheduling and Time Limitations. Thus, the general and special education teachers should intensify their collaboration and address the identified challenges. It is further recommended that a quantitative parallel study be conducted to validate and quantify the impacts of teacher collaboration strategies on the academic outcomes of learners with ASD.